Fåhræus effect revisited (Archives of Mechanics - Test, 2016)
A consistent hydrodynamic analysis of blood flow through capillaries is proposed. The approach, while suggested by empirical observations, is based solely on the properties of Newtonian fluids and suspensions. Blood flow is divided into three phases: the first is a thin erythrocyte-free layer near the wall, the second a core flow of constant hematocrit and the third an intermediate layer wherein the hematocrit varies. Based on the observation that viscosity depends exponentially on the local hematocrit, blood flow velocity profiles are obtained and the direct connection between the Fåhræus and the Fåhræus-Lindqvist effects is established.